2021
DOI: 10.31499/2616-5236.3(14).2020.234989
|View full text |Cite
|
Sign up to set email alerts
|

Research of consumer demand in the market of educational services of Dnipropetrovsk region

Abstract: The purpose of the research. The aim of the work is to study consumer needs in the market of educational services in marketing management system at higher educational institutions. Methods. The following methods were used in the research process: statistical – to process data on the dynamics of supply and demand; sociological – in the study of factors that affect individual and socio-economic demand; survey – to collect primary data on consumer demand in the market of educational services in Dnipropetrovsk reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Studies have emphasized the importance of understanding the needs and expectations of consumers, and the use of digital technologies to target potential customers. The focus on the Generation Z concept and the modelling of consumer behaviour in the educational market has been identified (Aleshnikova et al, 2020) as an important area for future research (Stebliuk & Kuzmenko, 2021). In conclusion, this study highlights the significance of continued marketing research and the need for HEIs to adapt to a constantly evolving competitive environment.…”
Section: Consumer Research In Heimentioning
confidence: 78%
“…Studies have emphasized the importance of understanding the needs and expectations of consumers, and the use of digital technologies to target potential customers. The focus on the Generation Z concept and the modelling of consumer behaviour in the educational market has been identified (Aleshnikova et al, 2020) as an important area for future research (Stebliuk & Kuzmenko, 2021). In conclusion, this study highlights the significance of continued marketing research and the need for HEIs to adapt to a constantly evolving competitive environment.…”
Section: Consumer Research In Heimentioning
confidence: 78%
“…The four Ps (product, price, place and promotion) which are the pillar of marketing requires market research in each pillar to help understand how these subjects work together in producing the most effective business and marketing strategy (Hague et al, 2013). It is also proved that with the help of marketing researches and modern approaches it is possible to get a clear idea of qualitative and quantitative criteria of demand, the real situation in the market; identify problems of interaction between different market participants; determine trends and directions of demand development; evaluate the effectiveness of information channels (Stebliuk & Kuzmenko, 2021). Adding to this, even a well-established international education such as the British colleges and universities did market research when they found there is a decreasing market penetration as competitors are emerging with quality education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The integrated model is established based on the Concept of diversification by analyses of multiple weighted consumer preferences to soften negative foreign countries' consumer' effects on Chinese education institutions to increase Chinese international education institutions' outperformance [5]. Performing an integrated consumer preference model is able to solve a puzzle; the players need the right pieces and the correct combination to achieve the desired outcomes [6]. The mainly used marketing theories are demonstrated as follows.…”
Section: Introductionmentioning
confidence: 99%